2017
DOI: 10.1089/ast.2015.1457
|View full text |Cite
|
Sign up to set email alerts
|

Survival and DNA Damage in Plant Seeds Exposed for 558 and 682 Days outside the International Space Station

Abstract: For life to survive outside the biosphere, it must be protected from UV light and other radiation by exterior shielding or through sufficient inherent resistance to survive without protection. We tested the plausibility of inherent resistance in plant seeds, reporting in a previous paper that Arabidopsis thaliana and tobacco (Nicotiana tabacum) seeds exposed for 558 days outside the International Space Station (ISS) germinated and developed into fertile plants after return to Earth. We have now measured struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Analysis of irradiated M 0 ANT and BNL seeds compared to non-irradiated seed samples showed that radiation damage significantly reduced the germination rates of the experimental groups, which is in line with previous studies despite the array of radiation conditions under which they were conducted (De Micco et al, 2011;Kranz, 1986;Tepfer and Leach, 2017;Tepfer et al, 2012). This also served to validate the ability of the BNL mixed-beam to faithfully reproduce this basic GCR effect, to the level that there was no significant difference found between the BNL and ANT M 0 germination rates.…”
Section: Impacts On Germination Ratessupporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of irradiated M 0 ANT and BNL seeds compared to non-irradiated seed samples showed that radiation damage significantly reduced the germination rates of the experimental groups, which is in line with previous studies despite the array of radiation conditions under which they were conducted (De Micco et al, 2011;Kranz, 1986;Tepfer and Leach, 2017;Tepfer et al, 2012). This also served to validate the ability of the BNL mixed-beam to faithfully reproduce this basic GCR effect, to the level that there was no significant difference found between the BNL and ANT M 0 germination rates.…”
Section: Impacts On Germination Ratessupporting
confidence: 89%
“…Seeds, including those of the model organism Arabidopsis thaliana, have historically served as a space-efficient biological recorder of radiation impact events in spaceflight conditions, with assessments of biological effects occurring postexposure through germination rates of irradiated seeds and frequencies of mutation (Kranz, 1986;Tepfer and Leach, 2017;Tepfer et al, 2012). The small genome size of A. thaliana (~135 Mbp) and the concomitant high gene density of 4.4 kb/gene (Wang et al, 2015) facilitate the identification of HZE-mutagenized individuals through an increased probability for coding sequence loss or rearrangement to result from damage.…”
Section: Introductionmentioning
confidence: 99%
“…Also angiosperms have been tested for irradiation resistance under space conditions: 23% of Arabidopsis thaliana and Nicotina tabacum seeds developed viable plants after space exposure in LEO for 558 days, receiving irradiation doses of 7.4 · 10 5 kJ$m -2 UV 110-400nm (Tepfer et al, 2012). However, when A. thaliana seeds were exposed to higher doses of 10.3 · 10 5 kJ$m -2 UV 110-400nm for 682 days at the ISS EXPOSE-R platform, seeds hardly survived (Novikova et al, 2015;Tepfer and Leach, 2017). YIELD from before the investigation was used as a factor and compared with Yield values at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, more realistic simulation scenarios can be achieved by long-time exposure of similar molecules as we have used herein in the International Space Station (ISS) facilities to address the effect of multiple radiation types, energies, and dosages. Examples of such studies have been reported (Cockell et al , 2011 ; Horneck et al , 2012 ; Tepfer and Leach, 2017 ) where phototrophic biofilms, B. subtilis spores, or plant seeds have been exposed to space conditions in the ISS for >600 days. However, simulating radiation doses equivalent to millions of years of accumulative radiation on a planetary-relevant environment is extremely complicated, mainly due to the low ionizing radiation rates at the ISS and the large amount of time of use that would be required to simulate planetary timescales.…”
Section: Discussionmentioning
confidence: 99%